SOUTH AMERICAN RPRESENTATIVE DEMOCRACY:: GOVERNABILITY DIELMMA IN PROGRESSIVE GOVERNMENTS - Biserra Maia, José Gilberto (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2024)
This study analyzes governance challenges in progressive governments in the representative democracy of Peru, Chile, Colombia and Brazil, with emphasis on citizenship via electoral participation. It’s a qualitative and exploratory research, developed through bibliographical and documentary research and reports in digital media that cover and reflect the Latin American region. It starts from the understanding that electoral formalities, which establish political representation, have been insufficient to meet society’s demands. A reality that has led to citizen apathy towards politics and electoral choices that are contradictory to their interests, observed in the compositions of the legislative powers of the respective countries, disconnected from the victorius political project at the polls. Such a scenario of representation disregards citizenchip as a political power, hinders governability, puts the progressive project at risk, and weakens the expectation of a fairer, more equitable and particpatory Latin America. Keywords: Representative Democracy. Citizenship. Elections. Governability. Latin  America.